The Influence of Transformational Leadership Style and Big Five Personality on Organizational Citizenship Behavior in Civil Servants of West Nusa Tenggara Province - Zulkarnaen, Iskandar (Journal of Social Science and Education Research, 2024)
This study aims to analyze the influence of Transformational Leadership Style and the Big Five Personality traits on Organizational Citizenship Behavior (OCB) among Civil Servants (ASN) in the Health Department, the Population and Civil Registration Department, and the National Population and Family Planning Agency in Mataram City and West Lombok Regency, West Nusa Tenggara Province. The Transformational Leadership Style is measured using the Multifactor Leadership Questionnaire (MLQ) Form 5X, which encompasses four main dimensions: idealized influence/charisma, individualized consideration, inspirational motivation, and intellectual stimulation. Meanwhile, the Big Five Personality traits include Neuroticism, Extraversion, Openness, Agreeableness, and Conscientiousness. This research employs a quantitative method with a survey approach. The study sample consists of 233 respondents selected based on Isaac and Michael's sample size determination table, with a 5% error level. Data is analyzed using multiple regression to determine the influence of each independent variable on the dependent variable. The results show that Transformational Leadership Style, Extraversion, Openness, Agreeableness, and Conscientiousness significantly influence OCB, whereas Neuroticism does not have a significant influence. Overall, Transformational Leadership Style and the Big Five Personality traits collectively have a significant influence on OCB. This study provides important contributions to the understanding of factors influencing OCB in the public sector, particularly within the context of the NTB Provincial Government. The managerial implications of these findings include the importance of developing supportive leadership styles and nurturing certain personality traits to encourage voluntary behaviors beneficial to the organization. Further research could explore other potential factors influencing OCB in the ASN work environment.